Association of beta-blockers beyond 1 year after myocardial infarction for patients without heart failure or left ventricular systolic dysfunction and cardiovascular outcomes: nationwide cohort study. (3rd October 2022) - Ishak, D; Aktaa, S; Lindhagen, L; Alfredsson, J; Dondo, T B; Held, C; Jernberg, T; Yndigegn, T; Gale, C P; Batra, G
Abstract: Background: Beta-blockers (BB) is an established treatment following presentation with myocardial infarction (MI). However, there is uncertainty as to whether BB use beyond the first year of MI has a secondary preventive role in patients without heart failure and/or left ventricular systolic dysfunction (LVSD). Purpose: To investigate the association between BB treatment beyond one year after MI for patients without heart failure or LVSD and cardiovascular (CV) outcomes. Methods: We used data from SWEDEHEART, the national Swedish register for coronary heart disease, to identify patients with MI who were hospitalised between 2005 and 2016. Deterministic linkage of individual patient data was performed with the National Patient Register, the Swedish Prescribed Drug Register, and the National Cause of Death Register. Patients with heart failure or LVSD with left ventricular ejection fraction <50% were excluded. Follow-up started at 1 year after hospitalisation with first MI (index date), when patients were allocated into two groups according to BB treatment. Information about BB treatment at index date and during follow-up was obtained from the Swedish National Prescribed Drug Register. The primary outcome was a composite of all-cause mortality, recurrent MI, unscheduled revascularisation or hospitalisation for heart failure. Secondary outcomes comprised the individual components of the composite outcome, CV death and stroke. Comparison of outcomes between the study groups was performed using Cox and Fine-Gray regression models adjusting for relevant clinical factors after propensity-score weighting. In the main intention-to-treat analysis, patients were censored at end of follow-up (31st December 2017), death or at pre-specified outcome, whichever came first. In supplementary per-protocol analysis, patients were, in addition, censored at the time of first BB discontinuation or switch between treatment arms. Results: A total of 43, 618 patients with MI were hospitalised between 2005 and 2016. Of these, 34, 253 (78.5%) were prescribed BB and 9, 365 (21.5%) were not on BB treatment at index date 1 year following MI. The median age of the population was 64 years, 25.5% were female, and 36.2% had a STEMI. Median follow-up was 4.5 years. In the intention-to-treat analysis, and after multivariable adjustments and propensity score weighting, BB treatment was associated with a similar rate of the composite CV outcome (hazard ratio [HR] 0.99; 95% confidence interval [CI] 0.93–1.04) compared with no BB treatment. A similar finding was observed when censoring for BB discontinuation or treatment switch during follow-up in a per-protocol analysis (HR 0.98; 95% CI 0.98–1.06). Similar associations were observed for all secondary outcomes (Figure 1). Conclusions: BB treatment beyond one year after MI for patients without heart failure or LVSD is not associated with a different risk of cardiovascular outcomes compared with patients who do not receive BB. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The study was financed by grants from the Swedish state under the agreement between the Swedish government and the county councils, the ALF-agreement.